(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Embedding a hidden stream of bits in a file is called Digital watermarking. The file could be an image, audio, video or text. Nowadays, a digital watermarking has many applications such as broadcast monitoring, owner identification, proof of ownership, transaction tracking, content authentication, copy control, device control and file reconstruction. It is intended to complement cryptographic processes. It is a visible or preferably invisible, identification code that is permanently embedded in the data and remains present within the data after any decryption process. The focus of this paper will detail digital watermarking for multimedia applications and covered by definition of digital watermarking, purpose, techniques and types of watermarking attacks briefly discussed.